2010
DOI: 10.1016/j.psychres.2008.10.027
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of night eating syndrome and binge eating disorder among overweight and obese individuals with serious mental illness

Abstract: The prevalence of night eating syndrome (NES) and binge eating disorder (BED) was assessed among overweight and obese, weight-loss-seeking individuals with serious mental illness (SMI). Sixty-eight consecutive overweight (BMI≥25 kg/m2) and obese (BMI≥30 kg/m2) individuals with SMI (mean age=43.9 years; mean BMI=37.2 kg/2; 67.6% Caucasian, 60.3% female) who were enrolled in a group behavioral weight loss treatment program were assessed at baseline for NES and BED with clinician-administered diagnostic interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
3
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 33 publications
1
60
3
2
Order By: Relevance
“…But, our figure is higher than that of Lundgreen et al, who reported the prevalence as 12.3% among general psychiatric samples [5]. Another study of Ludgren et al reported a NES rate of 40% when diagnosis was based on the proposed diagnostic criteria in patients with serious mental illnesses [6]. This difference may be due to the cultural factors or severity of psychiatric illness severity in the study sample.…”
Section: Discussioncontrasting
confidence: 76%
See 4 more Smart Citations
“…But, our figure is higher than that of Lundgreen et al, who reported the prevalence as 12.3% among general psychiatric samples [5]. Another study of Ludgren et al reported a NES rate of 40% when diagnosis was based on the proposed diagnostic criteria in patients with serious mental illnesses [6]. This difference may be due to the cultural factors or severity of psychiatric illness severity in the study sample.…”
Section: Discussioncontrasting
confidence: 76%
“…those with a BMI of ≥30 kg/m 2 ) were five times more likely to meet the criteria for NES compared to non-obese (i.e. those with a BMI of 18.5-25.9 kg/m 2 ) psychiatric patients [6]. BMI was not found to be significantly different between psychiatric participants with-NES and without-NES in the previous studies [6][7][8].…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations